AN ANALYSIS OF STUDENTS’ PERSONALITY TRAITS AND LANGUAGE LEARNING STRATEGIES - Aminah, Aminah; Mayuasti, Mayuasti; Putri, Dian Mega (TELL - US JOURNAL, 2017)
The purpose of this research is to analyze students’ personality traits and language learning strategies at the tenth grade students of SMK N 9 Padang academic year 2016/2017. Design of this study is descriptive qualitative. There are 25 students at the tenth grade of SMK N 9 Padang was becoming the respondents of this study which were chosen by stratified random sampling technique. The data was collected by using Big Five Inventory and Strategy Inventory for Language Learning version 7.0 (SILL) questionnaires. As the result, it found that there are various characteristics of the tenth grade students of SMK N 9 Padang academic year 2016/2017 are extraversion, agreeableness, conscientiousness, neuroticism and openness.  In addition, each of personality traits used different learning strategies where extraversion and agreeableness students use affective strategy, meanwhile, conscientiousness, neuroticism and openness use metacognitive strategy.